Application Effect of ICG Fluorescence Real-Time Imaging Technology in Laparoscopic Hepatectomy - Chen, Hao; Wang, Yumin; Xie, Zhiguo; Zhang, Luyuan; Ge, Yongsheng; Yu, Jihai; Zhang, Chuanhai; Jia, Weidong; Ma, Jinliang; Liu, Wenbin (Frontiers in Oncology, 2022)
This study aimed to evaluate the efficiency and safety of indocyanine green (ICG) fluorescence real-time imaging-guided technology in laparoscopic hepatectomy. A retrospective analysis of patients with primary liver cancer in the First Affiliated Hospital of USTC from January 2018 to October 2021, including 48 cases of fluorescence-guided laparoscopic hepatectomy (FGLH) and 60 cases of traditional laparoscopic hepatectomy (LH), was conducted. R0 resection rate, operation time, intraoperative blood loss, complications, hospital stay, and other intraoperative and postoperative indicators of the two groups were analyzed to determine the clinical feasibility and safety of ICG fluorescence real-time imaging-guided technology in laparoscopic hepatectomy. Related databases were searched for retrospective cohort studies and randomized controlled trials comparing FGLH with LH, studies were screened according to preset inclusion and exclusion criteria, literature quality was evaluated, and data were extracted. RevMan 5.3 software was used to conduct a meta-analysis on the extracted data. The results of our clinical data and meta-analysis showed that compared with LH, FGLH increased the R0 resection rate, shortened the operation time and postoperative hospital stay, and reduced blood loss and the occurrence of postoperative complications. Compared with LH, FGLH has a better application effect in laparoscopic hepatectomy, and it is worthy of promotion as it is safe and feasible.